Enhancement of ATRA-induced differentiation of neuroblastoma cells with LOX/COX inhibitors: an expression profiling study - Chlapek, Petr; Redova, Martina; Zitterbart, Karel; Hermanova, Marketa; Sterba, Jaroslav; Veselska, Renata (Journal of experimental & clinical cancer research, 2010)
BACKGROUND: We performed expression profiling of two neuroblastoma cell lines, SK-N-BE(2) and SH-SY5Y, after combined treatment with all-trans retinoic acid (ATRA) and inhibitors of lipoxygenases (LOX) and cyclooxygenases (COX). This study is a continuation of our previous work confirming the possibility of enhancing ATRA-induced cell differentiation in these cell lines by the application of LOX/COX inhibitors and brings more detailed information concerning the mechanisms of the enhancement of ATRA-induced differentiation of neuroblastoma cells. METHODS: Caffeic acid, as an inhibitor of 5-lipoxygenase, and celecoxib, as an inhibitor on cyclooxygenase-2, were used in this study. Expression profiling was performed using Human Cancer Oligo GEArray membranes that cover 440 cancer-related genes. RESULTS: Cluster analyses of the changes in gene expression showed the concentration-dependent increase in genes known to be involved in the process of retinoid-induced neuronal differentiation, especially in cytoskeleton remodeling. These changes were detected in both cell lines, and they were independent of the type of specific inhibitors, suggesting a common mechanism of ATRA-induced differentiation enhancement. Furthermore, we also found overexpression of some genes in the same cell line (SK-N-BE(2) or SH-SY5Y) after combined treatment with both ATRA and CA, or ATRA and CX. Finally, we also detected that gene expression was changed after treatment with the same inhibitor (CA or CX) in combination with ATRA in both cell lines. CONCLUSIONS: Obtained results confirmed our initial hypothesis of the common mechanism of enhancement in ATRA-induced cell differentiation via inhibition of arachidonic acid metabolic pathway.
Keywords: buněčná diferenciace; pyrazoly; Oxidative Stress; Cyclooxygenase Inhibitors; nádory mozku; oxidační stres; regulace genové exprese u nádorů; Humans; neuroblastom; multigenová rodina; Brain Neoplasms; sulfonamidy; Celecoxib; inhibitory cyklooxygenasy; lidé; Sulfonamides; kyseliny kávové; celekoxib; inhibitory lipoxygenas; Lipoxygenase Inhibitors; stanovení celkové genové exprese; Cell Differentiation; inhibitory enzymů; Neuroblastoma; Gene Expression Profiling; Tretinoin; Gene Expression Regulation, Neoplastic; Pyrazoles; Enzyme Inhibitors; Caffeic Acids; tretinoin; Multigene Family